La yuca en la alimentacion de cerdos - Maner, JH (International Center for Tropical Agriculture, 1972)
Research results obtained by the Cassava and Swine programs at the Instituto Colombiano Agropecuario are discussed. Low HCN var. should be used for swine feeding; the most promising var. is Llanera, which can yield 78 t/ha/10 mo and has a high crude protein content (7.25 percent). Balanced diets using the fresh roots or meal + different protein supplements are given for the life cycle of the swine: gestation, lactation, growing and finishing periods. When using CM, molasses should be added to make it more acceptable to the pigs; fresh roots should be supplied on a daily basis since they ferment rapidly. (CIAT)